2021
DOI: 10.3390/ijms23010129
|View full text |Cite
|
Sign up to set email alerts
|

CLDN6 Suppresses c–MYC–Mediated Aerobic Glycolysis to Inhibit Proliferation by TAZ in Breast Cancer

Abstract: Claudin 6 (CLDN6) was found to be a breast cancer suppressor gene, which is lowly expressed in breast cancer and inhibits breast cancer cell proliferation upon overexpression. However, the mechanism by which CLDN6 inhibits breast cancer proliferation is unclear. Here, we investigated this issue and elucidated the molecular mechanisms by which CLDN6 inhibits breast cancer proliferation. First, we verified that CLDN6 was lowly expressed in breast cancer tissues and that patients with lower CLDN6 expression had a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…In addition, the energy required for tumor cell invasion and migration can be continuously supported by aerobic glycolysis. Reprogramming glucose metabolism from oxidative phosphorylation to aerobic glycolysis to promote cancer growth, a phenomenon known as the 'Warburg effect,' is a specific hallmark of tumor cell metabolism (8). Various enzymes and signaling molecules involved in aerobic glycolysis have been reported to have an important role in the malignant development of tumors (9).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the energy required for tumor cell invasion and migration can be continuously supported by aerobic glycolysis. Reprogramming glucose metabolism from oxidative phosphorylation to aerobic glycolysis to promote cancer growth, a phenomenon known as the 'Warburg effect,' is a specific hallmark of tumor cell metabolism (8). Various enzymes and signaling molecules involved in aerobic glycolysis have been reported to have an important role in the malignant development of tumors (9).…”
Section: Introductionmentioning
confidence: 99%
“…Confocal images of TAZ localization showed that hiltonol induced a significant cytoplasmic sequestration of TAZ, corresponding to the dose of hiltonol, in both NK-92 ( Figure 2A ) and hNK cells ( Figure 2B ), but without affecting cell viability ( Figure S3B ). Interestingly, in control resting NK cells, TAZ was homogeneously present in both the cytoplasm and nucleus of NK cells, in contrast to being predominantly present in the nucleus of other adherent cell types [39][40] . To corroborate our observations, we treated NK-92 and hNK cells with hiltonol and performed imaging flow analysis to empirically quantify the overlap signal of nuclear stain (DAPI) to TAZ ( Figure 2C-F ).…”
Section: Resultsmentioning
confidence: 99%
“…The IF assay was performed as previously described [8]. Antibodies used in IF were listed in Supplementary materials.…”
Section: Immunofluorescent Staining (If)mentioning
confidence: 99%
“…CLDN6 is a member of the CLDNs family, containing four transmembrane helices and a COOHterminal PDZ-binding motif (PBM) [1]. In addition to traditional functions of CLDN6 in permeability regulation and barrier formation [2][3][4][5], CLDN6 connects proteins containing PDZ domain or PBM through its PBM, regulating intracellular signaling pathways to affect the malignant phenotype of cancer [6][7][8][9][10][11]. Previously, we have cloned CLDN6 as a candidate suppressor gene of breast cancer from COP rat mammary epithelial cells for the first time [12].…”
Section: Introductionmentioning
confidence: 99%